Hubungan antara Kepuasa Pernikahan dengan Empty Nest Syndrome pada Wanita Dewasa Madya - Mutmainnah Mutmainnah; Dian Novita Siswanti; Eka Sufartianinsih Jafar (CV. ULIL ALBAB CORP, 2024)
Middle-aged women are in the empty nest syndrome phase, a period when their children no longer live with them or have moved away. This can lead to various symptoms such as loneliness, loss, and emptiness. One significant factor that can affect the level of empty nest syndrome is marital satisfaction. This study aims to examine the relationship between marital satisfaction and empty nest syndrome in middle-aged women. This research uses a quantitative method. The subjects in this study are middle-aged women who have been left by all their children and are now living only with their husbands, with a total of 60 subjects. The results of the study show that there is a significant negative relationship between marital satisfaction and empty nest syndrome (r = -0.60, p < 0.05). This means that the higher the level of marital satisfaction, the lower the symptoms of empty nest syndrome experienced by middle-aged women. The implications of this research can be a reference for educational institutions and organizations to provide education regarding marital satisfaction so that they can minimize the impact of empty nest syndrome.